2017
DOI: 10.1007/978-3-662-54365-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Provably Secure NTRU Instances over Prime Cyclotomic Rings

Abstract: Due to its remarkable performance and potential resistance to quantum attacks, NTRUEncrypt has drawn much attention recently; it also has been standardized by IEEE. However, classical NTRUEncrypt lacks a strong security guarantee and its security still relies on heuristic arguments. At Eurocrypt 2011, Stehlé and Steinfeld first proposed a variant of NTRUEncrypt with a security reduction from standard problems on ideal lattices. This variant is restricted to the family of rings Z[X]/(X n + 1) with n a power of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…NTRU variants working with different rings. An NTRU variant that works with polynomials with prime cyclotomic rings was proposed in [35]. A variant of NTRU working with non-invertible polynomials was proposed in [22].…”
Section: Review Of Known Ntru Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…NTRU variants working with different rings. An NTRU variant that works with polynomials with prime cyclotomic rings was proposed in [35]. A variant of NTRU working with non-invertible polynomials was proposed in [22].…”
Section: Review Of Known Ntru Variantsmentioning
confidence: 99%
“…NTRU and its known variants [7,8,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], shown in Section 2, work with degree N polynomials. The main problem NTRU faces is that it is susceptible to the lattice basis reduction attack (LBRA) using the Gaussian lattice reduction (GLR) algorithm for two-dimensional lattices and the LLL algorithm for higher dimensions [39].…”
Section: Introductionmentioning
confidence: 99%
“…2011 年, Stehlé 和 Steinfeld [65] 在形如 Z[x]/(x 2 m + 1) 的环上建立了可 证明安全的 NTRU, 这个构造的抗量子性质目前也受到关注. 在更一般分圆环上可证明安全的 NTRU 的构造由 Yu 等 [66] 、Wang 和 Wang [67] 给出.…”
Section: Ntruunclassified
“…The RLWE represents an algebraic variant of the LWE [21] , whose hardness can be reduced to the hardness of the worstcase problems on ideal lattices in the standard model. However, recently, it has been shown that subfield attacks [22][23][24][25] affected the asymptotic security of NTRUtype schemes for large moduli q: Yu et al [26,27] considered a variant of NTRU encrypt over prime cyclotomic rings and obtained the INDistinguish-ability under Chosen-Plaintext Attack (IND-CPA) secure results in the standard model assuming the hardness of the worstcase problems on ideal lattices, which was shown to be a good choice to resist the subfield attacks.…”
Section: Introductionmentioning
confidence: 99%